2003
DOI: 10.4319/lo.2003.48.2.0656
|View full text |Cite
|
Sign up to set email alerts
|

Population growth and transport of the red tide dinoflagellate, Noctiluca scintillans, in the coastal waters off Sydney Australia, using cell diameter as a tracer

Abstract: Spatial abundance patterns of the heterotrophic dinoflagellate, Noctiluca scintillans, were investigated along the southeast coast of Australia to address the hypothesis that population growth of Noctiluca is driven by anthropogenic eutrophication. Abundance patterns were related to the immediate physical flow field and not the conditions conducive to growth. Noctiluca cells were advected southward with the East Australian Current, which was the dominant transport vector for the cells in this region. Areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 32 publications
0
12
0
3
Order By: Relevance
“…The climatology is an average, and concurrently shows scenarios that are normally separate and distinct. However, this transport of tropical EAC waters into southern coastal regions explains the biological connectivity occasionally observed along the NSW coast southward of the EAC separation point (e.g., Delacruz et al 2003).…”
Section: ) Across-shore Releasementioning
confidence: 95%
“…The climatology is an average, and concurrently shows scenarios that are normally separate and distinct. However, this transport of tropical EAC waters into southern coastal regions explains the biological connectivity occasionally observed along the NSW coast southward of the EAC separation point (e.g., Delacruz et al 2003).…”
Section: ) Across-shore Releasementioning
confidence: 95%
“…In a previous study we found that the EAC has the potential to advect Noctiluca cells away from the original area that might have stimulated population growth (Dela-Cruz et al, 2003). Here we also suggest that the southward flow of the EAC may partly explain the gradual increase in the abundance of Noctiluca from Smoky Cape to Diamond Head.…”
Section: Influence Of Eac Speed and Flow On The Abundance Of Noctilucmentioning
confidence: 56%
“…The red tides have been observed over a wide range of the coast (30-36°S), although greater than 90% were observed off Sydney, Australia's largest city (Ajani et al, 2001;Dela-Cruz et al, 2003). Previous field studies have indicated that the abundance of Noctiluca in Sydney's coastal waters is highest during the spring and summer (Murray & Suthers, 1999;Dela-Cruz et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Average total subresolved particle counts in all size classes from three replicate measurements using the OPC‐1L were between 0.3 and 6.2 L −1 for filtrate. Unfiltered water from the entrances to the estuarine systems had the highest number of particle counts of up to ∼30 L −1 , likely a result of high concentrations of the red tide forming dinoflagellate, Noctiluca scintillans , observed at these sites during this study and previous studies [ Dela‐Cruz et al , 2003]. Factor analysis was used to determine if there were groupings of particle counts from unfiltered water and filtrate.…”
Section: Resultsmentioning
confidence: 73%